Il preumanesimo di Rolandino - Costamagna, Giorgio (Scrineum, 2013)
Here is offered the last essay of Giorgio Costamagna (1916-2000), that was never printed before. He talks about notarial culture in the larger sense, developing some consideration by mean of Rolandino de’ Passaggeri’s Summa totius artis notarie and the analysis of firmulae available in cartularies and documents (especially of Genua) of XIIth and 13th Century; his arguments are framed in the context of medieval political and philosophical thought.